ANALISIS STRATEGI PEMASARAN DIGITAL PANGAN LOKAL ENBAL DI KOTA TUAL - Martha Cyclop Putry Reimialy; Natelda R Timisela; Tienni M Simanjorang (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2026)
This research aims to analyze the digital marketing strategy for enbal local food in Tual City by reviewing obstacles, formulating strategies, and determining the main strategies that can be applied by home industry players (IRT). The research approach uses a descriptive qualitative method utilizing SWOT analysis to identify strengths, weaknesses, opportunities, and threats in enbal digital marketing. The results show that the main strengths of enbal products lie in the uniqueness of raw materials, distinctive taste, and cultural value, while weaknesses include low digital literacy of business actors, limited packaging, and production capacity. In terms of opportunities, the increasing trend of local food consumption, high use of social media, and government support for digitalization of MSMEs are driving factors. The threats come from competition with modern food products, high distribution costs in the archipelago, and low interest of young generation in traditional food. Based on SWOT mapping, the recommended main strategies are strengthening digital branding, improving packaging quality, developing creative promotion content, and enhancing digital capabilities of business actors. This research is expected to be a reference for MSME players in optimizing digital marketing to expand market access and increase the competitiveness of enbal products in Tual City. Keywords: digital marketing, enbal, marketing strategy, SWOT, MSME